COHESION AND COHERENCE OF ONLINE NEWS CNN INDONESIA DISCOURSE REGARDING THE MURDER CASE OF A FRIED SNACK SELLER IN PARIAMAN, WEST SUMATRA: A DISCOURSE ANALYSIS - Randi, Randi; Sari, Nur Indah (Journal of Education for The Language and Literature of Indonesia, 2025)
The ease of accessing information makes it difficult to clarify the truth of the news being reported. One of the right ways to filter information is by conducting cohesion and coherence analysis.This research aims to understand how cohesion and coherence are used in online news regarding the viral case of the fried food vendor murder in Pariaman, West Sumatra, that occurred some time ago. Cohesion and coherence are important criteria and principles in a text. This research is expected to contribute to the development of story writing quality. So that the story can be understood and useful for the readers. Thus, the purpose of writing the story can inspire readers. The method used to analyze cohesion and coherence is descriptive analysis, which is evident in each paragraph. The aspect of cohesion that is analyzed is the aspect of lexical cohesion and grammatical cohesion. The results of this study show that the story "Regarding the murder case of a fried food seller in Pariaman, West Sumatra" in the criminal news on the online media CNN Indonesia on Saturday, September 14, 2024, has aspects of lexical cohesion, grammatical cohesion, and coherence. The aspect of constructive cohesion and coherence where discourse can convey a message to the reader. In this way, the content of the story can make the readers feel what the writer feels.